The history of renovation design of the front facade of the Main Post Office Building in Lublin - Pytlarz, Elżbieta (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
In this article it is presented a ranovation process of the Post Office building in Lublin held in 2001 – 2003. The location of thic edifice in the main street and the same time of the frontage of the central square raises the status of this building particularly that its facade is the background of numerous official celebrations and meetings of the authorities and citizens of Lublin. The author of this article describes designing solutions and also the cooperation process of architect, client, conservator and performer. The photographs showing the facade of the Main Post Office building in Lublin before its restauration and the effect after it enable a reader to compare the facade of the building from the past to its contemporary state.